2020
DOI: 10.4018/978-1-7998-3042-9.ch006
|View full text |Cite
|
Sign up to set email alerts
|

The Affective Economy and Online Fan Communities

Abstract: This chapter explores participation and co-production in affective media experiences in Johnny & Associates' online fan communities. Johnny & Associates is a Japanese all-male talent management company established in the 1960s. As a pioneer in the idol industry, Johnny & Associates and artists under its management have been highly influential in the contemporary Japanese entertainment industry. These artists are collectively known as Johnny's idols or Janīzu. Much of the data are collected through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
1
0
2
Order By: Relevance
“…Notably, the cost associated with nurturing internal talent for fan marketing is typically significantly lower than the fees associated with hiring external celebrities for endorsements. This financial efficiency can be a compelling factor in shaping a company's star strategy, especially for businesses seeking to maximize the return on their marketing investments [9,10].…”
Section: The Feasibility Of the Star Employee + Product Strategymentioning
confidence: 99%
“…Notably, the cost associated with nurturing internal talent for fan marketing is typically significantly lower than the fees associated with hiring external celebrities for endorsements. This financial efficiency can be a compelling factor in shaping a company's star strategy, especially for businesses seeking to maximize the return on their marketing investments [9,10].…”
Section: The Feasibility Of the Star Employee + Product Strategymentioning
confidence: 99%
“…Previously, studies have been conducted on fan-related activities, and results have shown that the expressive activities of idols allow fans to gain cultural capital. It is a brand-new way to build social connections with celebrities, make fans feel close to their idols, and impart knowledge to fans through "collective wisdom" (Mansor et al, 2020). One of the more typical examples is the star-making process of the Chinese idol Lee.…”
Section: Idols and Fans Progress Togethermentioning
confidence: 99%
“…Las evidencias marcadas en los estudios sobre subculturas o fandoms del pasado muestran que, en su mayoría, las relaciones o reacciones emocionales de los miembros no suelen tomarse como prioridad; sin embargo, en la actualidad, otros muchos estudios han incorporado la perspectiva del afecto para investigar el fenómeno, como, por ejemplo, la economía afectiva (Mansor et al, 2020) o la recepción afectiva (Lamerichs, 2018). En este artículo, creo que las intervenciones y libertades de expresión de los dark académicos son cruciales para entender la esencia del paradigma al que nos enfrentamos, pues permiten a los investigadores acceder directamente a las voces, las articulaciones y las interpretaciones de algunos aficionados (Bennett, 2017, p.36).…”
Section: La Encuesta Y Sus Preguntasunclassified